Importance of a specialized pathologist for the examination of frozen sections of adnexal masses. Issue 5 (1st September 2007) - Fanfani, F.; Zannoni, G. F.; Fagotti, A.; Gagliardi, M. L.; Masciullo, V.; Testa, A. C.; Scambia, G.
Abstract : The aim of the present study was to examine the impact of a specialized pathologist on the accuracy of frozen section analysis for adnexal masses. We included women who underwent frozen section diagnosis for adnexal mass surgery. A specialized and a general pathologist read the sections. We calculated sensitivity, specificity, positive and negative predictive values, and accuracy for the whole series, as well as for the specialized and general pathologist groups. We included 325 patients; in 103 patients (31.7%), frozen section diagnosis was performed by the specialized and in 222 (68.3%), by the general pathologist. There was a significant difference in terms of correspondence between the specialized and the general pathologist groups ( P = 0.024). We registered four overdiagnoses (both performed by the general pathologist [1.8% vs 0%]) and 56 underdiagnoses of which 14 (13.6%) were made by the specialized pathologist and 46 (20.7%) by the general pathologist. In 14 cases (4.3%), diagnosis could not be made on frozen section and was postponed to final histology for definitive diagnosis (1/103 [0.9%] for the specialized pathologist and 13/222 [5.8%] for the general pathologist). Our data confirm previous reports on the accuracy of frozen section analysis of adnexal masses and show a significant positive impact of the specialized pathologist as opposed to the general pathologist.